Impact of mixed silages of licorice aerial parts and whole plant corn on nutrient digestibility, rumen fermentation, and gastrointestinal microbiota in Simmental cattle - Liu, Haonan; Tang, Limin; Xu, Xingyu; Gao, Qifeng; Sun, Yuliang; Li, Wenhao; Lu, Dong; Yu, Houjun; Jiang, Tao (Frontiers in Veterinary Science, 2025)
IntroductionLicorice aerial parts are widely cultivated in China but often underutilized due to nutrient loss during haymaking. Ensiling with whole-plant corn may enhance their nutritional value and utilization in ruminant diets.MethodsThis study evaluated the effects of mixed silages containing aerial parts of licorice and whole-plant corn at inclusion levels of 0, 22, 28, and 34% on nutrient digestibility, rumen fermentation, and gastrointestinal microbiota in Simmental cattle. Forty-eight male Simmental cattle were randomly assigned to four groups and fed the experimental diets for 75 days. Apparent nutrient digestibility, rumen fermentation parameters, and microbial profiles in rumen fluid and feces were analyzed.ResultsThe 22% and 28% silage groups showed significantly higher digestibility of neutral detergent fiber (NDf) and acid detergent filber (ADF), along with increased concentrations of rumen acetate and total volatile fatty acids (TVFA), compared to the control and 34% groups. Rumen pH was significantly lower in these groups. Microbial diversity (Chao1 index increased inthe 34% group, while the 22% group exhibited a higher relative abundance of beneficial rumen bacteria such as Oscillospiraceae and NK4A214 group, with Oscillospiraceae negatively correlated with rumen pH. in feces, Firmicutes was enriched in the 28%group and identified as a key biomarker, Other beneficial taxa, including Christensenellaceae, Monoglobaceae and Ruminococcus, also increased with silage supplementation.Discussion/conclusionThese findings suggest that incorporating 28% licorice-corn mixed silage into the diet optimizes nutrient digestibility, enhances rumen fermentation, and improves gut microbial composition, thereby boosting feeding efficiency in fattening Simmental cattle.